PENERAPAN MODEL PEMBELAJARAN IKRAR (INISIASI, KONSTRUKSI- REKONSTRUKSI, APLIKASI, REFLEKSI) UNTUK MENGURANGI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA POKOK BAHASAN PERSAMAAN LINIER SATU VARIABEL - Syafi’i, Moh. Imam (Kadikma, 2014)
Abstract.There are manystudentswhohave difficultyin solvingmath problems. The difficultiescausedinstudentsa mistakein solvingproblems.The types of student’s mistakesare the use of misused data, misinterpretated language, logically invalid inference, distorted theorem,unverified solution,and technical error. Therefore, appliedIKRAR learning modelis urgently needed todecrease thestudent’smistakes in solvingLinear Equation of One Variable problems at seventhgradeMTs Negeri Kalibaruacademic year2013/2014. This research design is Classroom Action Research (CAR).The result show that the percentage ofeffectivenesson the first cycle of 31,02 % and 41,80 % for the second cycle. So it can be concluded that the application of IKRAR learning model type is effective enough to overcome student’s mistakesin solving Linear Equation of One Variable. Keywords: IKRAR learning model, Linear Equation of One Variable, student’s activity, student’s mistakes